Double trouble: does co-morbid chronic somatic illness increase risk for recurrence in depression? A systematic review. - Gemma D Kok; Claudi L H Bockting; Huibert Burger; Wiebke Hannig; Gerdina H M Pijnenborg; Pim Cuijpers; Steven D Hollon (PLoS ONE)
Objective To perform a systematic review, and if possible a meta-analysis, to establish whether depressed patients with co-morbid chronic somatic illnesses are a high risk "double trouble" group for depressive recurrence. Method The databases PubMed, EMbase and PsycINFO were systematically searched until the 4(th) of December 2012 by using MeSH and free text terms. Additionally, reference lists of retrieved publications and treatment guidelines were reviewed, and experts were consulted. Inclusion criteria were: depression had to be measured at least twice during the study with qualified instruments and the chronic somatic illness had to be assessed by self-report or by a medical professional. Information on depressive recurrence was extracted and additionally risk ratios of recurrence were calculated. Results The search generated four articles that fulfilled our inclusion criteria. These studies showed no differences in recurrence over one- two- three- and 6.5 years of follow-up for a total of 2010 depressed patients of which 694 patients with a co-morbid chronic somatic illness versus 1316 patients without (Study 1: RR = 0.49, 95% CI, 0.17-1.41 at one year follow-up and RR = 1.37, 95% CI, 0.78-2.41 at two year follow-up; Study 2: RR = 0.94, 95% CI, 0.65-1.36 at two year follow-up; Study 3: RR = 1.15, 95% CI, 0.40-3.27 at one year follow-up; RR = 1.07, 95% CI, 0.48-2.42 at two year follow-up and RR = 0.99, 95% CI,0.55-1.77 at 6.5 years follow-up; Study 4: RR = 1.16, 95% CI, 0.86-1.57 at three year follow-up). Conclusion We found no association between a heightened risk for depressive recurrence and co-morbid chronic somatic illnesses. There is a need for more longitudinal studies to justify the current specific treatment advice such as long-term pharmacological maintenance treatment for this presumed "double trouble" group.